Pengaruh Green marketing Terhadap Keputusan Pembelian The Body Shop melalui Green trust sebagai Variabel Mediasi - Kencana Wulan; Dede Kurnia; Azizah Fauziyah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Increasing environmental awareness among consumers has encouraged companies to implement sustainable marketing strategies, one of which is throughgreen marketing. The Body Shopis a cosmetics brand that prioritizes environmentally friendly values ​​across its entire product line. However, the effectiveness of its strategygreen marketingin driving purchasing decisions, it is not necessarily optimal without consumer trust in the company's green commitment, or what is known as the termgreen trust. The population and sample in this study are product usersThe Body Shopwho live in Jabodetabek. This study aims to examine the influence ofgreen marketing to product purchase decisions The Body Shop, with green trustas a mediating variable. The study used a quantitative approach with a survey method for user respondents.The Body Shopin Indonesia. The data analysis technique used is Structural Equation Modeling (SEM) on the SmartPLS application. The results of the study show thatgreen trusthas a positive and significant influence as a mediator betweengreen marketing and product purchase decisions The Body Shopin Greater Jakarta. Green trust serves as a psychological bridge that bridges the relationship between marketing stimuli and consumer purchasing decisions.